2020
DOI: 10.21203/rs.3.rs-60070/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of Post-Traumatic Stress Disorder after Coronavirus Disease

Abstract: Background There was an outbreak of coronavirus disease (COVID-19) in Daegu, the Republic of Korea, in 2020. We investigated the prevalence of post-traumatic stress disorder (PTSD) among patients with COVID-19 who were treated and discharged at a university hospital in Daegu, Korea. Methods A total of 64 patients who were diagnosed with COVID-19 and hospitalized, treated, and discharged from a university hospital between February and April 2020 participated to our study. We conducted a phone interview and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Several recent studies have investigated PTSD in the specific context of the coronavirus outbreak. Among patients recovering from the coronavirus disease, the proportion with symptom-defined PTSD have varied between 12.4% and 31.0% [ 11 , 12 , 13 , 14 , 15 ]. Liu and co-workers [ 11 ] found that the risk of PTSD was associated with disease severity and perceived stigma related to the disease, whereas Cai and co-workers [ 12 ] found lower PTSD rates among patients over 60 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have investigated PTSD in the specific context of the coronavirus outbreak. Among patients recovering from the coronavirus disease, the proportion with symptom-defined PTSD have varied between 12.4% and 31.0% [ 11 , 12 , 13 , 14 , 15 ]. Liu and co-workers [ 11 ] found that the risk of PTSD was associated with disease severity and perceived stigma related to the disease, whereas Cai and co-workers [ 12 ] found lower PTSD rates among patients over 60 years old.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, PTSD in the population may be frequent during the pandemic and may be linked to specific concerns related to the COVID-19 context. While several studies have examined PTSD in the coronavirus context [ 11 , 12 , 13 , 14 , 15 , 16 ], many are hampered by relatively small sample sizes and samples representing specific contexts such as hospitals or geographical regions. Moreover, the research focus has largely been placed on infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller study of 64 COVID-19 patients found that 20.3% met the criteria for PTSD following hospitalization. 44 Since then, a study of the electronic health records of nearly 70 million patients from 54 healthcare organizations in U.S. found that 18.1% of patients hospitalized for COVID-19 were diagnosed with a psychiatric condition in the 14 to 90 days following COVID-19 diagnosis, including 5.8% who received first-time psychiatric diagnosis. 45 By comparison, less than half the percentage (2.8%) of individuals from a matched cohort of hospitalized influenza patients were diagnosed with a psychiatric condition in the same interval.…”
Section: Contributors To Psychological Distressmentioning
confidence: 99%
“…A smaller study of 64 COVID-19 patients found that 20.3% met the criteria for PTSD following hospitalization. 44…”
Section: Contributors To Psychological Distressmentioning
confidence: 99%
“…Other studies report high frequencies of PTS, but do not clearly describe COVID-19 severity. Wesemann et al ( 2020 ) used the PCL-5 and found significant PTS in 8/19 (42%) COVID-19 patients shortly after their presentation to hospital, whereas Chang and Park ( 2020 ) used the PCL-5 to identify PTS in 13/64 (20%) patients assessed 10 weeks after discharge. Either study neither described COVID-19 severity nor indicated the requirement for critical care.…”
mentioning
confidence: 99%